‘Different spaces, different laws’: The role of state forums in non-state dispute processing in India - Kokal, Kalindi (Comparative Dispute Resolution, 2020)
This Chapter explores dispute processing in a fishermen’s village in the state of Maharashtra in western India. Her essay explores the manner in which spaces of the state, such as police stations and state courts, were considered and used by the Kol_i_ community in the village. Building upon empirical data she argues “that such use of spaces and places of the state reveals another translation of state law … and the manner in which it is optimized.” The ‘space’ at the core of this chapter is multidimensional in both its abstract and more tangible dimensions. But it also comprises different imaginations of space in between the spheres of the state and non-state. Thus, Kokal suggests, dispute processing represents an important site “that reveals the forms of use of these spaces, which are in themselves expressions of the manner in which laws are constituted and interpreted.”
Created from Fastlane, Scopus look-up